Relatório final do estágio curricular obrigatório do curso de Medicina Veterinária, realizado junto ao serviço de nutrição clínica de cães e gatos do Hospital Veterinário Governador Laudo Natel, Jaboticabal - SP. Relato de caso: shunt porto-hepático em cães e gatos - Sarteschi, Natalia Pelliqueiro [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Mandatory internship report in Veterinary Medicine, in the Service of Nutrition and Clinical Nutrition of dogs and cats, through which the activities carried out with the sector are described, in the clinical routine of care of patients who were referred by the medical clinic, as well as care of the patient returns. In the daily routine of the sector, nutritional therapeutic measures were developed together with the residents, as well as the formulation of both homemade and commercial diets. At the end of the report, a case of interest was chosen, which consists of a literature review and a case report treated at the clinic during the internship period.

Relatório de estágio obrigatório em Medicina Veterinária, no Serviço de Nutrição e Nutrição clínica de cães e gatos, através do mesmo são descritas as atividades realizadas junto ao setor, na rotina clinica de atendimento dos pacientes que foram encaminhados pela clinica médica, bem como atendimento dos retornos dos pacientes. No cotidiano do setor era elaborado junto às residentes medidas terapêuticas nutricionais, como também formulação de dietas tanto caseiras como comerciais. No final do relatório escolheu-se um caso de interesse que consiste em revisão de literatura e relato do caso atendido na clinica durante o período do estágio.
Final report of the mandatory curriculum internship of the Veterinary Medicine course, held at the Clinical Nutrition Service of Dogs and Cats of the Governador Laudo Natel Veterinary Hospital, Jaboticabal - SP. Case report: port hepatic shunt in dogs and cats
Keywords: Cães; Gatos; Nutrição animal